A modified rapid access heuristic for flowshop scheduling problem. (1st January 2011) - Wang, Ning; Moraga, Reinaldo J.; Ghrayeb, Omar
This paper presents a modified rapid access (MRA) heuristic to solve the flowshop scheduling problems. This new heuristic follows the fundamental idea of the original rapid access approach by forming a two-machine subproblem, but the processing times are determined by using an exponential weighting modifier for the original linear weighting scheme without additional computational effort, then the subproblem is solved by using Johnson's two-machine algorithm. The performance of MRA is tested using instances from the literature and compared with the performance of the original rapid access (RA). Results show that the MRA outperforms the original RA in large size problems by using specific value of parameter alpha. Factorial experiment and response surface methodology are applied to determine the best alpha value which is the main factor that impacts the performance of MRA and produce the best performance of the MRA heuristic.